“MORPHOLOGICAL AND MORPHOMETRIC ANALYSIS OF CYSTIC FIBROSIS IN CHILDREN IN UZBEKISTAN.” - Karataeva Lola Abdullaevna; Rakhmonova Shakhnoz Kakhhorovna (Western European Studies, 2025)
Cystic fibrosis or cystic fibrosis or Landsteiner-Fanconi disease is a hereditary systemic autosomal recessive exocrinopathy, characterized by early clinical manifestations of the respiratory tract, gastrointestinal system and other organs. Among all the diseases that occur in newborns, cystic fibrosis occurs in 1 in 2 thousand children
Keywords: cystic fibrosis; intestinal form; immunohistochemistry